JAPANESE WISTERIA AND KAWUNG MOTIFS AS THE DEVELOPMENT OF BATIK FOR ART WEAR - Widi, Sayekti Nugrahaning; -, Septianti (Runtas: Jurnal Fesyen dan Wastra Nusantara, 2023)
Batik has various kinds of motifs. They are traditional and developed motifs. The combination of wisteria and kawung motifs for art wear is a work inspired by hokokai batik. It is a result of acculturation between Japan and Indonesia. Japanese wisteria (Wisteria Floribunda) is a kind of flower that grows in Japan. In Japan, it is called Fuji. The wisteria flower symbolizes loyalty, nobility, and immortality. Furthermore, kawung motif is a motif developed in Indonesia, especially in Java. It has a meaning of sedulur papat lima pancer. This article aims to batik by combining two motifs, wisteria, and kawung. These two motifs would be applied in art wear. Exploration is the first stage in creating this work. It starts from looking for some references of kawung motif and wisteria motif. The second is the design stage. In this stage, the creator designs motifs that would be chosen in some alternatives as a motif would be applied in art wear. The last stage is manifestation. Making batik motifs begins with making patterns, nyorek, nyanting, coloring, and, melorod. This creation results in four works. The first is titled Hi. The second is titled Kaze. The third is titled Ki. The fourth is titled Mizu. These four titles represent four elements ruled by the four guardian gods of the cardinal directions. The four gods are legends from Japan.